Corner-sharing tetrahedra for modeling micro-structure. (September 2019) - Sitharam, Meera; Youngquist, Jeremy; Nolan, Maxwell; Peters, Jörg
Abstract: This paper introduces Corner-Sharing Tetrahedra (CoSTs), a minimalist, constraint-graph representation of micro-structure. CoSTs have built-in structural guarantees, such as connectivity and minimal rigidity. CoSTs form a space, fully accessible via local operations, that is rich enough to design regular or irregular micro-structure at multiple scales within curved objects. All operations are based on efficient local graph manipulation, which also enables efficient analysis and adjustment of static physical properties. Geometric and material detail, parametric or solid splines, can be added locally, on-demand, for example, for printing. Highlights: Corner-Sharing Tetrahedra (CoSTs) a graph-based model of micro-structure. CoSTs have built-in structural guarantees, such as connectivity and minimal rigidity. The rich space of CoST allows designing micro-structure at multiple scales within curved objects. CoSTs support efficient analysis and adjustment of static physics. Geometric and material detail, parametric or solid splines are added locally, on-demand.